Structure and Physical Properties of PZT-PMnN-PSN Ceramics Near the Morphological Phase Boundary - Nguyen Dinh Tung Luan; Le Dai Vuong; Truong Van Chuong; Nguyen Truong Tho (Advances in Materials Science and Engineering)
The 0.9Pb(ZrxTi1−x)O3-0.07Pb(Mn1/3Nb2/3)O3-0.03Pb(Sb1/2Nb1/2)O3 (PZT-PMnN-PSN) ceramics were prepared by columbite method. The phase structure of the ceramic samples was analyzed. Results show that the pure perovskite phase is in all ceramics specimens. The effect of the Zr/Ti ratio on the region of morphotropic phase boundary for PZT-PMnN-PSN ceramics was studied. Experimental results show that the phase structure of ceramics changes from tetragonal to rhombohedral with the increase of the content of Zr/Ti ratio in the system. The composition of PZT-PMnN-PSN ceramics near the morphotropic phase boundary obtained is the ratio of Zr/Ti: 49/51. At this ratio, the ceramic has the optimal electromechanical properties: the kp=0.61, the εmax=29520, the d31=-236 pC/N, the Qm=2400, high remanent polarization (Pr=49.2 μC·cm−2), and low coercive field Ec=10.28 kV·cm−1.